2008
DOI: 10.1186/1746-4269-4-23
|View full text |Cite
|
Sign up to set email alerts
|

Living knowledge of the healing plants: Ethno-phytotherapy in the Chepang communities from the Mid-Hills of Nepal

Abstract: Contribution of indigenous knowledge in developing more effective drugs with minimum or no side effects helped to realise importance of study of indigenous remedies and the conservation of biological resources. This study analysed indigenous knowledge regarding medicinal plants use among the Chepang communities from ward number 3 and 4 of Shaktikhor Village Development Committee located in the central mid hills of Nepal. Data were collected in a one-year period and included interviews with traditional healers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…6). Our findings resembled with other studies amongst Chepang community in Chitwan district (Rijal, 2008), Rai and Tamang community in Sunsari district (Deokota and Chhetri, 2009), Tamang community in Rasuwa district (Upreti et al, 2010), Tharu and Magar community in Rupendehi district (Singh et al, 2012)and Tamang communityin Makawanpur district (Luitel et al, 2014).…”
Section: Plant Parts Usedsupporting
confidence: 94%
“…6). Our findings resembled with other studies amongst Chepang community in Chitwan district (Rijal, 2008), Rai and Tamang community in Sunsari district (Deokota and Chhetri, 2009), Tamang community in Rasuwa district (Upreti et al, 2010), Tharu and Magar community in Rupendehi district (Singh et al, 2012)and Tamang communityin Makawanpur district (Luitel et al, 2014).…”
Section: Plant Parts Usedsupporting
confidence: 94%
“…Forest products not only provide the rural population with subsistence needs like fuel wood, fodder, and litter, but also provide wild foods during the periods of food shortage when the grain storage starts dwindling and the new harvest is not yet available (see Khatri-Chhetri, 2006, Piya et al, 2011a). Many NTFPs also have medicinal (Rijal, 2008) and socio-cultural values (Aryal, 2007). Besides these subsistence uses, trade of NTFPs form a source of cash income for many of the rural population in Nepal (Chhetri and Gupta, 2006;Edwards, 1996;.…”
Section: Introductionmentioning
confidence: 99%
“…The Czech Republic has quite a high rate (67%) of picking mushrooms compared to other western European countries, e.g., in Denmark, the picking rate is only 4% [13,20,65]; however, the information was not collected in this study. Nevertheless, the study confirmed that forestry plays a less vital role in the food availability of the respondents unlike in Asian or African countries [66][67][68].…”
Section: Frequency Of the Forest Visits According To The Driversmentioning
confidence: 55%